GENERATIONAL TRAUMA IN SHERMAN ALEXIE’S AND JEROME ROTHENBERG’S SELECTED POETRY - Ahmed, Ala (Humanities Journal of University of Zakho, 2024)
Jewish and Native American history is widely recognized to have many similarities. The catastrophic events of the Holocaust and Native American colonization created trauma for centuries. This article attempts to investigate the portrayal of generational trauma in Sherman Alexie’s and Jerome Rothenberg’s poetry. Generational trauma refers to a trauma that has been inherited from one generation to another. It does not necessarily mean that an individual has to go through a direct traumatic event him/herself. Rather, it is transmitted through secondary memory which refers to recollecting memory and storytelling. Cathy Caruth’s psychoanalytical theory Unacclaimed Experience (1996) on historical trauma is utilized while analyzing the selected poems. Alexie and Rothenberg write poetry about their heritage, history, ancestors, and cultures. Moreover, this article aims to show how Rothenberg depicts the struggles of second/third-generation of Holocaust survivors, their detachment from their homelands, and the memory of the past. As well as investigating Alexie’s characterization of the issues related to Natives’ communities: such as alcoholism, sexual abuse, drug use, and family dysfunctions. These problems have existed hundreds of years after colonization.